Cataract Surgery in Highly Myopic Eyes (Global Journal of Medical Research, 2020)
Myopia affects approximately 25% of the population. High myopia is defined by a refractive error of more than -6D or an axial length of more than 26 mm (1-3), it is accompanied by degenerative changes in the eye tissues. It is recognized as a risk factor for the onset of cataracts. (4) Our present work aims to assess the difficulties, peculiarities, and complications of cataract surgery in highly myopic eyes. Materials and methods: We conducted a prospective comparative study, were included 79 highly myopic patients scheduled for cataract surgery (LAgt; 26 mm) and 80 patients candidates for cataract surgery as a control group. Patients with pseudo-exfoliation, glaucomatous syndrome, operated for retinal detachment, or with a history of uveitis were excluded. Statistical analysis was performed by SPSS software.
Keywords: cataract; phacoemulsification; high myopia